2019
DOI: 10.5194/hess-23-2541-2019
|View full text |Cite
|
Sign up to set email alerts
|

Observation operators for assimilation of satellite observations in fluvial inundation forecasting

Abstract: Abstract. Images from satellite-based synthetic aperture radar (SAR) instruments contain large amounts of information about the position of floodwater during a river flood event. This observational information typically covers a large spatial area but is only relevant for a short time if water levels are changing rapidly. Data assimilation allows us to combine valuable SAR-derived observed information with continuous predictions from a computational hydrodynamic model and thus to produce a better forecast than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…In our study none of the model state variables is updated as only the particle weights are computed, based on the SAR observations and on the simulated flood extent maps, and used to calculate the expectation of water levels and streamflow. In previous studies (Andreadis et al, 2007;Matgen et al, 2010;Cooper et al, 2019), inflow updating was identified as a condition leading to more persistent improvements. For instance, one of the conclusions from the study by Matgen et al (2010) was that updating the fluxes at the upstream boundary conditions, rather than the water levels, is more effective because of the high uncertainty of the inflow due to the poorly known rainfall distribution over the catchment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our study none of the model state variables is updated as only the particle weights are computed, based on the SAR observations and on the simulated flood extent maps, and used to calculate the expectation of water levels and streamflow. In previous studies (Andreadis et al, 2007;Matgen et al, 2010;Cooper et al, 2019), inflow updating was identified as a condition leading to more persistent improvements. For instance, one of the conclusions from the study by Matgen et al (2010) was that updating the fluxes at the upstream boundary conditions, rather than the water levels, is more effective because of the high uncertainty of the inflow due to the poorly known rainfall distribution over the catchment.…”
Section: Discussionmentioning
confidence: 90%
“…In the existing literature only a few studies have used DA for directly assimilating flood extent maps into flood forecasting models (e.g., Lai et al, 2014;Revilla-Romero et al, 2016;Cooper et al, 2019Cooper et al, , 2018Hostache et al, 2018). Among the advantages of a direct use of the SAR backscatter values is that it reduces the data processing time, which is a key element in near-operational applications.…”
Section: Introductionmentioning
confidence: 99%
“…as reported in Cooper et al (2019). The nearly-direct use of the SAR information has the additional advantage of a faster processing from the acquisition to the assimilation of the SAR image being therefore suitable for operational needs.…”
Section: Discussionmentioning
confidence: 99%
“…5 A second use is to provide near real-time data for assimilation into urban flood inundation models, to correct the model state, and improve estimates of the model parameters and external forcing. [6][7][8][9][10][11][12][13] A substantial amount of research has been carried out on automated flood detection in rural areas. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Several organisations, including the Copernicus Emergency Management Service (EMS), have developed semi-automatic systems to extract the flood extent from an SAR image.…”
Section: Introductionmentioning
confidence: 99%